A Multimodal Genotoxic Anticancer Drug Characterized by Pharmacogenetic Analysis in Caenorhabditis elegans. Issue 3 (1st July 2020) - Ye, Frank B; Hamza, Akil; Singh, Tejomayee; Flibotte, Stephane; Hieter, Philip; O'Neil, Nigel J
Abstract: New anticancer therapeutics require extensive in vivo characterization to identify endogenous and exogenous factors affecting efficacy, to measure toxicity and mutagenicity, and to determine genotypes that result in therapeutic sensitivity or resistance. We used Caenorhabditis elegans as a platform with which to characterize properties of the anticancer therapeutic CX-5461. To understand the processes that respond to CX-5461-induced damage, we generated pharmacogenetic profiles for a panel of C. elegans DNA replication and repair mutants with common DNA-damaging agents for comparison with the profile of CX-5461. We found that multiple repair pathways, including homology-directed repair, microhomology-mediated end joining, nucleotide excision repair, and translesion synthesis, were needed for CX-5461 tolerance. To determine the frequency and spectrum of CX-5461-induced mutations, we used a genetic balancer to capture CX-5461-induced mutations. We found that CX-5461 is mutagenic, resulting in both large copy number variations and a high frequency of single-nucleotide variations (SNVs), which are consistent with the pharmacogenetic profile for CX-5461. Whole-genome sequencing of CX-5461-exposed animals found that CX-5461-induced SNVs exhibited a distinct mutational signature. We also phenocopied the CX-5461 photoreactivity observed in clinical trials and demonstrated that CX-5461 generates reactive oxygen species when exposed to UVA radiation. Together, the data from C. elegans demonstrate that CX-5461 is a multimodal DNA-damaging anticancer agent.